Center Finding in E. coli and the Role of Mathematical Modeling: Past, Present and Future. Issue 5 (1st March 2019) - Murray, Seán M.; Howard, Martin
Abstract: We review the key role played by mathematical modeling in elucidating two center-finding patterning systems in Escherichia coli : midcell division positioning by the MinCDE system and DNA partitioning by the ParABS system. We focus particularly on how, despite much experimental effort, these systems were simply too complex to unravel by experiments alone, and instead required key injections of quantitative, mathematical thinking. We conclude the review by analyzing the frequency of modeling approaches in microbiology over time. We find that while such methods are increasing in popularity, they are still probably heavily under-utilized for optimal progress on complex biological questions. Graphical Abstract: Unlabelled Image Highlights: The role of mathematical modeling is reviewed in bacterial MinCDE and ParABS systems. Modeling has contributed central ideas helping to uncover mechanisms in both cases. MinCDE system implements mass-conserving dynamical instability giving oscillations. ParABS system may implement a flux-balance mechanism for regular plasmid placement. Modeling can inject key ideas but is still highly under-utilized in microbiology.